Experimental Impacts of a Virtual Parenting Program with Mothers and Fathers - Lara Lebedinski; Pedro Carneiro; Tamara Arnold Urzua; Julie Perng; Ana María Mu\~noz Boudet; Katia Herrera Sosa (Institute of Labor Economics (IZA), 2024)
In this paper we evaluate experimentally the impacts of a parenting program delivered virtually to 1,431 families with children ages 2-6 years old in Serbia. We compare two program modalities to a control group. In the first (standard) modality, only the main caregiver -mainly mothers- participates in the training, while in the second (plus), two caregivers -mothers and fathers- participate in the training. We find that the standard intervention has a positive effect of 0.28 standard deviations on parent-reported child development outcomes, but no such impact is found for the plus modality. We fail to observe statistically significant impacts of either treatment across most variables measuring parental behaviors and home environments, with two exceptions: parents in the standard treatment became more conscious about their child's learning, while parents in the plus modality became less likely to use physical punishment to discipline children.
Keywords: I10; 330; parenting program; child development; virtual delivery